Contract & Equity v Torrens System - Sethu, R.R. (Journal of Malaysian and Comparative Law, 2019)
The decision of the Supreme Court in Lee Yoke Chye v Toh Theam Hock & Co (a firm) is the latest addition to the continued conflict and rivalry between the torrens sytem and the conveyancing practice. The torrens system cannot completely abrogate or replace the conveyancing practice which is ostensibly adopted and dressed as a contract between the parties. The courts have sought to harmonize the two: that the contracts and equitable relief is provided to complete or perfect them within the torrens system. The inevitable practice is that in the torrens land transactions in this country a contract of sale and a loan agreement precede the transfer and a charge in the case of banks. The contracts govern the rights of the respective parties pending and after completion in respect of charges, and in some cases of, transfers.